Analisis Kesulitan Belajar Siswa dengan Taksonomi Solo - Anis Umi Khoirotunnisa; Ahmad Kholiqul Amin; M. Taufiqurrohman (Jurnal Pendidikan Edutama, 2022)
Analysis of learning difficulties needs to be done as one of the evaluations process in the classroom. With this difficulty analysis the teacher can diagnose the types of difficulties experienced by students, the results of this research are expected to be a reference for improvement of learning process. To analyze student difficulties, the SOLO taxonomy theory is used which divides the level of student error in solving problems from the first level, namely prestructural, unistructural, multistructural, relational and extended abstract. This error level classification is seen from the student's work in solving the problem of flat shapes which contains 10 questions describing the material. Students were randomly selected from all grade VII MTs SA Miftahul Hikmah located in Parengan sub-district, Tuban district, East Java. The data analysis technique uses source triangulation, where the test results are validated by interviewing students based on the level of errors made. From the results of data analysis and interviews, it was concluded that students had difficulties at the prestructural, unistructural and multistructural levels. Based on this research, students with low initial abilities are at the level of prestructural and unistructural errors, students have difficulty interpreting the questions so that they have difficulty determining the problem solving to be used, then students with initial abilities are having difficulties at the multistructural and relational levels and students with high initial ability tends to only have difficulty extended Abstract or making conclusions.Keyword: difficulties, SOLO Taxonomy, shapes.Analisis kesulitan belajar perlu untuk dilakukan sebagai salah satu proses evaluasi di kelas. Dengan adanya analisis kesulitan ini guru dapat mendiagnosis tipe kesulitan yang dialami siswa, hasil kajian ini nantinya diharapkan dapat menjadi acuan pembenahan proses pembelajaran. Untuk menganalisis kesulitan siswa digunakan digunakan teori Taksonomi SOLO yang membagi level kesalahan pengerjaan siswa dalam menyelesaikan masalah dari level pertama yakni prastruktrural, Unistruktural, Multistruktural, Relasional dan Extended Abstract. Pengklasifikasian level kesalahan ini dilihat dari pekerjaan siswa dalam menyelesaikan maslah bangun datar yang berisi 10 soal uraian pada materi tersebut. Siswa dipilih secara random dari seluruh kelas VII MTs SA Miftahul Hikmah yang berada di kecamatan Parengan Kabupaten Tuban, Jawa Timur. Teknik Analisis Data menggunakan Triangulasi sumber, dimana dari hasil tes di validasi dengan wawancara kepada siswa berdasarkan level kesalahan yang dilakukan. Dari hasil analisis data dan wawancara didapatkan hasil kesimpulan bahwa siswa mengalami kesulitan pada level prastruktural, Unistruktural dan Multistruktural. Berdasarkan penelitan ini, siswa dengan kemampuan awal rendah berada pada level kesalahan  prastruktural dan unistruktural siswa mengalami kesulitan dalam menginterpretasikan soal sehingga mengalami kesulitan menentukan pemecahan masalah yang akan digunakan, selanjutnya pada siswa dengan kemampuan awal sedang melakukan kesulitan pada level multistructural dan level relational dan siswa dengan kemampuan awal tinggi cenderung hanya mengalami kesulitan extended Abstract atau membuat kesimpulan.Kata kunci: Kesulitan, Taksonomi Solo, Bangun Datar.